Electrochemical behaviour of 5-benzyl-4-(4?-methylphenyl)-4H-1,2,4- triazole-3-thiol by voltammetry - Dilgin, Yusuf; Koparir, Metin; Çetin, Ahmet; Cansiz, Ahmet; Yilmaz, Selehattin; Giray, Didem (Indian Chemical Society, 2007)
The electrochemical study of a thiotriazole compound, 5-benzyl-4-(4?- methylphenyl-4H-1,2,4-triazole-3-thiol (TTA) was made with cyclic voltammetry (CV) and differential pulse voltammetry (DPV) using glassy carbon electrode (GCE) as working electrode and an Ag/AgCl reference electrode in the Britton- Robinson buffer. The best results for electrooxidation of TTA were obtained in basic media (in 10% ethanol-0.2 M NaOH). This compound display one irreversible oxidation peak, which is attributed to a dimerization process involving the formation of disulphide derivative (EC mechanism).
Keywords: Electrochemical behaviour; Glassy carbon electrode; Thiotriazole